2020
DOI: 10.1177/0886260520958390
|View full text |Cite
|
Sign up to set email alerts
|

Fear for All Women: European women’s fear of harassment and aggression in public spaces

Abstract: This work is based on the inequality that women suffer in public spaces, with fear being a constant in their lives. Women must learn to live to accept a limited and constrained existence. Based on this approach, this research establishes a European description and comparison of the insecurities, fears, or concerns expressed by women facing the risk of aggression/harassment, and the prevalence of sexual harassment in public spaces. For this, we used the Survey on Violence Against Women in the European Union (EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…The study also found that more harassment of women is reported in the most equal countries [3]. It may be explained as the more equal social environment encouraging more women to speak out about their suffering, but they also reported that they are more afraid of being attacked [3]. This paper aims to explain the reasons women are in a weak position objectively and subjectively in Europe, discuss the features which threaten women's perceived safety in the park and finally explore how landscape architects could contribute to improving the perceived safety of female visitors.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The study also found that more harassment of women is reported in the most equal countries [3]. It may be explained as the more equal social environment encouraging more women to speak out about their suffering, but they also reported that they are more afraid of being attacked [3]. This paper aims to explain the reasons women are in a weak position objectively and subjectively in Europe, discuss the features which threaten women's perceived safety in the park and finally explore how landscape architects could contribute to improving the perceived safety of female visitors.…”
Section: Introductionmentioning
confidence: 58%
“…It seems like researchers assume that Europe is a more equal and safer place for women. However, more than half of Europeans would not be able to enjoy certain spaces because of fear of crime [3]. The study also found that more harassment of women is reported in the most equal countries [3].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Una de las principales razones de la falta de prioridad que el gobierno concede al acoso sexual callejero es su efecto desproporcionado sobre las mujeres. Como se analiza brevemente a continuación, el feminismo dominante explica mejor las experiencias vividas por las mujeres que han sido víctimas de acoso sexual callejero (Moreno et al, 2022). Los estudios jurídicos críticos (CLS) también ayudan a explicar por qué a las mujeres se les niega el acceso pleno e igualitario a las protecciones legales y por qué la ley sistemáticamente desatiende a las comunidades menos poderosas.…”
Section: Teorías Académicas Relevantesunclassified
“…Digital Violence and Women: Systematization of Researchs and Suggestions For Future Research Although the literature has given great importance to various cyber crimes such as hacking, identity theft and online fraud in the previously studied subjects, issues such as partner violence, domestic violence and digital harassment have recently started to take place (Al-Alosi, 2017). Since it has been proven that women are more likely to be victims of domestic violence in public spaces (Moreno, Prados and Cuenca-Piqueras, 2022), it is thought that the tendency to experience digital violence will also be high. For example, according to the Digital Violence in Turkey Research conducted by the Turkish Social Information and Communication Association (2021); women stated that they were more exposed to digital violence because of their gender (52%) and physical appearance (21%), and men because of their political views (30%).…”
Section: Introductionmentioning
confidence: 99%